Mesenchymal Meis2 controls whisker development independently from trigeminal sensory innervation - Kaplan, Mehmet Mahsum; Hudacova, Erika; Matejcek, Miroslav; Tuaima, Haneen; Křivánek, Jan; Machon, Ondrej (eLife, 2025)
Hair follicle development is initiated by reciprocal molecular interactions between the placode-forming epithelium and the underlying mesenchyme. Cell fate transformation in dermal fibroblasts generates a cell niche for placode induction by activation of signaling pathways WNT, EDA, and FGF in the epithelium. These successive paracrine epithelial signals initiate dermal condensation in the underlying mesenchyme. Although epithelial signaling from the placode to mesenchyme is better described, little is known about primary mesenchymal signals resulting in placode induction. Using genetic approach in mice, we show that Meis2 expression in cells derived from the neural crest is critical for whisker formation and also for branching of trigeminal nerves. While whisker formation is independent of the trigeminal sensory innervation, MEIS2 in mesenchymal dermal cells orchestrates the initial steps of epithelial placode formation and subsequent dermal condensation. MEIS2 regulates the expression of transcription factor Foxd1, which is typical of pre-dermal condensation. However, deletion of Foxd1 does not affect whisker development. Overall, our data suggest an early role of mesenchymal MEIS2 during whisker formation and provide evidence that whiskers can normally develop in the absence of sensory innervation or Foxd1 expression.
Keywords: hair follicle placode; Neural Crest; Mesoderm; forkhead transkripční faktory; vývojová regulace genové exprese; developmental biology; cranial nerves; nervus trigeminus; Meis2; Gene Expression Regulation, Developmental; mouse; Trigeminal Nerve; Forkhead Transcription Factors; crista neuralis; Sox2; Animals; zvířata; Foxd1; Vibrissae; myši; vibrissae; mezoderm; Homeodomain Proteins; whisker follicle; Mice; homeodoménové proteiny